Clinical and Angiographic Characteristics of Coronary Heart Disease Patients at RS Jantung Jakarta - Putri, Keisha Azzura Gusmardi; Ruslim, Daniel (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2024)
Coronary Heart Disease (CHD) is a cardiovascular disease that impairs perfusion to the myocardium. Coronary Computed Tomography Angiography (CCTA) and Invasive Coronary Angiography (ICA) or commonly known as coronary catheterization are two possible modalities to visualize the coronary vessels in CHD patients. However, both of the modalities have their own advantages and disadvantages. This study aims to describe details of the stenosis severity frequencies in both modalities with the characteristics of these CHD patients at RS Jantung Jakarta. This study uses an observational descriptive method to assess the frequency distribution of stenosis severity in CHD patients that have completed CCTA and ICA examination at RS Jantung Jakarta with 369 patients, 1.476 coronary vessels, and 807 stenotic lesions in total. Sampling method of this study is consecutive sampling. Majority of CHD patients in this study were ≥60 years old and have obesity. Majority of the patients on this study reach the blood pressure target. Most of the patients have only one vessel with significant stenosis. Most vessel affected was LAD (Left Anterior Descending Artery). There’s 71.4% of the coronary vessels detected as severe stenosis on CCTA examination but only 50.4% of the coronary vessels detected as severe stenosis on ICA examination. It can’t be denied that although CT coronary angiography has high potential, it still can’t replace coronary catheterization (invasive coronary angiography) as the gold standard in determining the degree of coronary artery stenosis in CHD patients due to its limitation.